Experience and Challenges during Establishment of a Cyclotron and PET-CT facility at National Institute of Nuclear Medicine & Allied Sciences (NINMAS) - Islam, Md Nurul (Bangladesh Journal of Nuclear Medicine, 2021)
Abstract not available Bangladesh J. Nuclear Med. 22(2): 137-140, Jul 2019